Age-related changes in egg yolk composition between conventional and organic table eggs - Baykalir, Yasin; Simsek, Ulku Gulcihan; Yilmaz, Okkes (Scientific Agricultural Soc Finland, 2020)
The aim of this study was to investigate fatty acids, fat-soluble vitamins, malondialdehyde and cholesterol in conventional and organic eggs obtained from hens of different ages (30 and 60 weeks). A total of 360 egg yolks were used in this study. Polyunsaturated fatty acid, omega-3, and omega-6 levels were higher in the organic eggs from the 30-week-old hens. The monounsaturated fatty acid level was higher in the conventional eggs but was the same between the two age groups. Cholesterol and vitamin A levels were not influenced by either the rearing system or the age of the hens. The malondialdehyde, vitamin D2, and vitamin K2 were higher in the organic eggs; however, vitamin E was higher in the conventional eggs. The results showed that the rearing system and age, as well as the diet, had an impact on the composition of the egg. Total levels of polyunsaturated fatty acid, omega-3, and omega-6 are higher in organic eggs produced by younger hens.
Keywords: egg components; egg quality; laying hen; rearing system